A thousand splendid suns - Hosseini, Khaled (New York : Riverhead Books, 2009)
Afghan women Mariam and Laila grow close, despite their nearly twenty-year age difference and initial rivalry, as they suffer at the hands of a common enemy--their abusive, much-older husband, Rasheed.
Adult
Adult
830
Keywords: Afghanistan -- Fiction; Afghanistan -- Fiction